The syntax of time - Guéron, Jacqueline; Lecarme, Jacqueline (Current studies in linguistics series, 2004)
Any analysis of the syntax of time is based on a paradox: it must include a syntax-based theory of both tense construal and event construal. Yet while time is undimensional, events have a complex spatiotemporal structure that reflects their human participants. How can an event be flattened to fit into the linear time axis? Chomsky's The Minimalist Program, published in 1995, offers a way to address this problem. The studies collected in The Syntax of Time investigate whether problems concerning the construal of tense and aspect can be reduced to syntactic problems for which the basic mechanism and principles of generative grammar already provide solutions. These studies, recent work by leading international scholars in the field, offer varied perspectives on the syntax of tense and the temporal construal of events: models of tense interpretation, construal of verbal forms, temporal aspect versus lexical aspect, the relation between the event and its argument structure, and the interaction of case with aktionsart or tense construal. Advances in the theory of temporal interpretation in the sentence are also applied to the temporal interpretation of nominals.